EFFECT OF COVID-19’S SECOND WAVE ON THE NIGERIAN STOCK MARKET - Adaramola, Anthony Olugbenga; Kayode, Peter Akinyemi; Omotayo, Vincent Adewale; Ogiamien, Omoruyi Fidelis (APPS Publications, 2022)
This study examined the effect of the second wave of the Covid-19 pandemic from early December 2020 to March end, 2021 on the performance of the Nigeria Stock Exchange (NSE). We examined the effect from two perspectives: stock price and trade volume. On one side, the study investigated how the pandemic affected the aggregate stock price and volume of stocks traded on the other. The study used Autoregressive Distributed Lag (ARDL) technique to analyze the data of second-wave Covid-19 confirmed cases, number of related deaths versus All Share Index, and volume of stocks traded on both short and long-runs. Results showed that with respect to stock prices, in the short run, Covid-19 second wave confirmed cases and number of deaths have a positive but insignificant effect on stock prices. In the long run, the effect of confirmed cases on stock price was negative and insignificant, that of the number of deaths was positive but significant. With respect to the volume of trade on the NSE, in the short run, while the number of confirmed cases has a positive and significant effect on the volume of trade, the number of recorded deaths has a positive but insignificant effect. In the long run, however, the effect of both confirmed cases and the number of deaths is positive but statistically insignificant. We conclude that the Covid-19 second wave only significantly affects the volume of trade on the NSE and that the effect is positive but that the pandemic did not significantly affect stock prices.